Pengaruh pemberian asi terhadap lama masa nifas di puskesmas trucuk I - Eka Rati Astuti; R. Detty Siti Nurdiati; Dewi Rokhanawati (Universitas Aisyiyah Yogyakarta, 2016)
The study aims to analyze the influence of breast feeding towards the puerperal period in Primary Health Care Trucuk I Klaten in the year of 2015. This research is the type of analytical research that uses the design of retrospective cohort with the quantitative approach. The sample uses purposive sampling. The total sample are 86 mothers who breastfeed fully and 86 mothers who breastfeed partially. The result of the analysis shows that there are 103 (59,9%) cases of short peurperal period. The variable that significantly influence the puerperal period is breastfeeding (OR = 34,550; 95% CI = 12,925-92,353) and parity (OR = 0,404; 95% CI = 0,170-0,963). Meanwhile, the variables that have no significant influence the puerperal period is IMD (95% CI=0,756-11,045), mother age (95% CI = 0,221-1,096), and the status of mother employment (95% CI=0,744-2,731).